Pengaruh Iklan Digital Terhadap Minat Beli Konsumen di Angkringan Sedulur, Pekanbaru - Darmawati Darmawati; Anisa Febriyanti (Institut Nalanda, 2025)
This article discusses the effect of digital advertising on consumers' purchasing interests, focusing on Angkringan Sedulur in Pekanbaru. This study shows that informative, attractive, and easily accessible digital advertising can increase consumers' purchasing interest, although its influence is still relatively weak compared to other factors. Through a case study of Shopee and Tokopedia users, it was found that effective digital marketing strategies can increase brand awareness and encourage purchasing. Therefore, Angkringan Sedulur is advised to develop innovative and relevant digital advertising, as well as utilize social media to reach more customers. This study emphasizes the importance of regular evaluation of the effectiveness of digital advertising to increase sales and customer loyalty.